2013
DOI: 10.1038/ng.2554
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide meta-analyses of multiancestry cohorts identify multiple new susceptibility loci for refractive error and myopia

Abstract: Refractive error is the most common eye disorder worldwide, and a prominent cause of blindness. Myopia affects over 30% of Western populations, and up to 80% of Asians. The CREAM consortium conducted genome-wide meta-analyses including 37,382 individuals from 27 studies of European ancestry, and 8,376 from 5 Asian cohorts. We identified 16 new loci for refractive error in subjects of European ancestry, of which 8 were shared with Asians. Combined analysis revealed 8 additional loci. The new loci include genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
409
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 404 publications
(445 citation statements)
references
References 50 publications
25
409
2
4
Order By: Relevance
“…36 Genome-wide association studies identified single-nucleotide polymorphisms in several genes, such as GRIA4, KCNQ5, RDH5, LAMA2, BMP2, SIX6, PRSS56, GJD2, RASGRF1, ZC3H11B, and WNT7B, as risk factors for refractive error including myopia. [6][7][8] Although some of these genes (SIX6, PRSS56, and WNT7B) function in eye development, 7,8 it remains unclear how such sequence variants shape phenotypic variation. Phenotyping studies by using genetically engineered mice with different genetic backgrounds in conjunction with sequence analyses will provide useful information on the association between genomic and phenotypic variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Genome-wide association studies identified single-nucleotide polymorphisms in several genes, such as GRIA4, KCNQ5, RDH5, LAMA2, BMP2, SIX6, PRSS56, GJD2, RASGRF1, ZC3H11B, and WNT7B, as risk factors for refractive error including myopia. [6][7][8] Although some of these genes (SIX6, PRSS56, and WNT7B) function in eye development, 7,8 it remains unclear how such sequence variants shape phenotypic variation. Phenotyping studies by using genetically engineered mice with different genetic backgrounds in conjunction with sequence analyses will provide useful information on the association between genomic and phenotypic variations.…”
Section: Discussionmentioning
confidence: 99%
“…2 In humans, genome-wide association studies revealed new susceptibility loci for eye diseases, such as refractive error including myopia. [6][7][8] Over 450 inbred strains of mice have been described, 9 providing a wealth of different genotypes and phenotypes for studying human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In this GATES analysis, the strongest associated gene, PXDNL, did not reach genomewide significance (p = 3.42e-5). Our non-replication could be due to the fact that both the studies by Hysi et al (2010) and Verhoeven et al (2013) included larger samples. However, it is interesting to note that most SNPs that are strongly associated with mean spherical equivalent in our analyses, are most strongly (but not significantly) associated to both left and right eye sphere, and not to cylinder of either eye.…”
Section: Implementation: Myopia Datamentioning
confidence: 85%
“…Using MERLIN (Abecasis et al 2002) to analyze that data, the SNP rs8027411, located in the RASGRF1 gene, had the strongest (yet not genome-wide significant) association with spherical equivalent in (Hysi et al 2010) (p = 7.91e-8), and this SNP did reach genome-wide significance (p = 2.07e-9) in a replication sample of six cohorts combined. The RASGRF1 gene was also significantly associated with spherical equivalent in Verhoeven et al (2013). Behav Genet (2016 SNP rs8027411 was only included in our analyses when larger boundary extensions than 5 kb were used.…”
Section: Implementation: Myopia Datamentioning
confidence: 99%
See 1 more Smart Citation